HLA haplotypes in primary sclerosing cholangitis patients of admixed and non‐European ancestry - Henriksen, Ellen Karoline; Gotthardt, Daniel (HLA, 2017)
Primary sclerosing cholangitis (PSC) is strongly associated with several human leukocyte antigen (HLA) haplotypes. Due to extensive linkage disequilibrium and multiple polymorphic candidate genes in the HLA complex, identifying the alleles responsible for these associations has proven difficult. We aimed to evaluate whether studying populations of admixed or non-European descent could help in defining the causative HLA alleles. When assessing haplotypes carrying HLA-DRB1*13:01 (hypothesized to specifically increase the susceptibility to chronic cholangitis), we observed that every haplotype in the Scandinavian PSC population carried HLA-DQB1*06:03. In contrast, only 65% of HLA-DRB1*13:01 haplotypes in an admixed/non-European PSC population carried this allele, suggesting that further assessments of the PSC-associated haplotype HLA-DRB1*13:01?DQA1*01:03-DQB1*06:03 in admixed or multi?ethnic populations could aid in identifying the causative allele.